Hybrid Islanding Detection of an Inverter-Based High-Noise Microgrid - Hossein Amini; Ali Mehrizi-Sani; Reza Noroozian (IEEE Access)
Unintentional islanding occurs when a microgrid continues operating independently after disconnection from the main grid, which can lead to voltage and frequency instability, power quality degradation, and safety risks. Few local and remote methods consider islanding detection in noisy environments. Noise can interfere with measurements and cause failed or delayed islanding detection. This paper proposes a hybrid islanding detection method that utilizes a Van der Pol Duffing oscillator (VDPDO), focusing on decreasing the detection period, zero power mismatch nondetection zone, and power quality degradation. The proposed method uses the fast Fourier transform (FFT) symmetry characteristic of a hybrid VDPDO (HVDPDO) output signal and addresses the set point threshold using the Melnikov function. This method detects the changes in frequency, phase, and voltage amplitude of the point of common coupling (PCC) simultaneously to distinguish islanded operation from other faults. For the asymmetric FFT waveform of the passive HVDPDO, the islanding system sends a signal to the inverter to change the mode from grid-following to grid-forming and injects perturbations into the frequency, phase, and voltage amplitude, simultaneously. The active HVDPDO detects islanded operations with a small non-detection zone. The inverter reverts to grid-following mode for other faults, and the main grid damps the intentionally small perturbations. Simulation and experimental results validate that the proposed method meets the IEEE standard 1547 criteria.